Dependence of maxima in space. (21st January 2015) - Ferreira, H; Pereira, L
Abstract: We evaluate the dependence among large values of a spatial process of maxima trough a coefficient that can be applied in natural, technical and societal extreme phenomena. Its main properties are: a) k locations can be taken into account; b) it takes values in [0, 1] and higher values indicate stronger dependence; c) it is independent of the univariate marginal distributions of the random field; d) it can be related with other coefficients in the literature such as the tail dependence and the extremal coefficients; e) it agrees with the concordance property for multivariate distributions; f) it has as a particular case the variogram from geostatistics; g) it can be easily estimated. We illustrate the application of the introduced coefficient with the estimation of the degree of dependence among large values of the amount of tritium in drinking water for tree cities.